The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3389/fnbeh.2012.00077
|View full text |Cite
|
Sign up to set email alerts
|

Differential serotonergic modulation of two types of aggression in weakly electric fish

Abstract: Agonistic aggression has provided an excellent framework to study how conserved circuits and neurochemical mediators control species-specific and context-dependent behavior. The principal inhibitory control upon aggression is serotonin (5-HT) dependent, and the activation of 5-HT1A receptors is involved in its action. To address whether the serotonergic system differentially regulates different types of aggression, we used two species of weakly electric fish: the solitary Gymnotus omarorum and the gregarious B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 91 publications
2
34
0
Order By: Relevance
“…Territorial aggression of G. omarorum in intra-and intersexual interactions during the non-breeding season has been described previously (Batista et al, 2012;Silva et al, 2013;Zubizarreta et al, 2012Zubizarreta et al, , 2015. Accordingly, in this study, surgically-identified males displayed typical agonistic behavior in dyadic interactions (Fig.…”
Section: Male-male Non-breeding Territorial Aggressionmentioning
confidence: 65%
See 2 more Smart Citations
“…Territorial aggression of G. omarorum in intra-and intersexual interactions during the non-breeding season has been described previously (Batista et al, 2012;Silva et al, 2013;Zubizarreta et al, 2012Zubizarreta et al, , 2015. Accordingly, in this study, surgically-identified males displayed typical agonistic behavior in dyadic interactions (Fig.…”
Section: Male-male Non-breeding Territorial Aggressionmentioning
confidence: 65%
“…The electric signals depend on a very well-known and tractable neural circuit (Caputi et al, 2005;Stoddard, 2002), and the relative simplicity of this electromotor circuit offers important operational advantages for studying the neuroendocrine control of behavior. The non-breeding territorial aggression of G. omarorum constitutes a clear example of non-sex biased territorial aggression, unique among teleosts, in which we can precisely identify the phases of the agonistic encounter, the emergence of the dominance-subordination status, levels of aggression and an orderly sequence of submissive electric displays (Batista et al, 2012;Silva et al, 2013;Zubizarreta et al, 2012Zubizarreta et al, , 2015. The original description of the non-breeding agonistic behavior of G. omarorum showed that size asymmetry (but not individual sex nor dyad composition) predicted contest outcome (Batista et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the golden hamster, AVP facilitated offensive aggression in males, which can be blocked by pretreatment with a selective serotonin re-uptake inhibitor (SSRI) (Delville et al, 1996;Ferris and Delville, 1994) or 5-HTR 1A agonist (Ferris et al, 1999). A direct interaction between serotonergic and vasopressin neurons in the anterior hypothalamus of hamsters was described (Ferris et al, 1997) and the possibility of a similar case in the weakly electric fish Gymnotus omarorum was recently speculated (Zubizarreta et al, 2012). Using in situ hybridization, Greenwood et al demonstrated that in subordinate A. burtoni, AVT expression is higher in parvocellular neurons compared with dominant males (Greenwood et al, 2008).…”
Section: Serotonin and Sexual Behaviormentioning
confidence: 99%
“…The EOD of B. gauderio could serve as an indicator of body length because the amplitude of the signal physically depends on the length of the electric organ, which runs the length of the fish's body (Curtis and Stoddard, 2003;Hopkins, 1999;Hopkins et al, 1990). Moreover, body length is key for mate choice and male-male interactions, as longer males are more attractive to females (Curtis and Stoddard, 2003) and are more likely to win agonistic encounters (Salazar, 2009;Zubizarreta et al, 2012). Therefore, receivers should pay particular attention to any information about body length coded in the signal.…”
Section: Does Eod Modulation Degrade Its Reliability As An Honest Indmentioning
confidence: 99%